Cobalt-based catalyst for producing ammonia through catalytic oxidation of nitrous oxide and nitric oxide as well as preparation method and application of cobalt-based catalyst
By preparing a cobalt-based catalyst and applying it to electrocatalysis, the problems of efficient N2O removal and synergistic conversion of N2O and CO2 were solved, realizing ammonia synthesis with low energy consumption and low carbon emissions, and exhibiting excellent catalytic activity and stability.
Patent Information
- Application Number
- CN202511320204.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-26
AI Technical Summary
In existing technologies, the removal of N2O requires a large amount of heat and may generate secondary pollution. At the same time, the reaction mechanism and performance optimization of cobalt-based catalysts in the electrocatalytic reduction of N2O to NH3 and the synergistic conversion of N2O and CO2 have not been thoroughly studied.
A method for preparing cobalt-based catalysts involves mixing a cobalt source, carbon-nitrogen compounds, and a precipitant, followed by hydrothermal reaction and pyrolysis to prepare a cobalt-based catalyst, which is then applied to the electrocatalytic production of ammonia from nitrogen-containing compounds and the synergistic electrocatalytic production of urea from N2O and CO2.
The efficient and low-energy electrocatalytic conversion of N2O to NH3 under ambient temperature and pressure was achieved, exhibiting excellent catalytic activity and stability. In particular, the Co/NC-800 catalyst achieved an NH3 yield of 58.73 mg mental-1 h-1 and a Faraday efficiency of 48.08% under -0.25 V conditions.
Smart Images

Figure CN121198334A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of catalysts and environmental pollution, and particularly relates to a cobalt-based catalyst for catalytic oxidation of nitrous oxide and nitrogen oxide to produce ammonia, a preparation method and application. BACKGROUND
[0002] Nitrous oxide (N2O) is a long-lived stratospheric ozone-depleting substance and greenhouse gas, with a longer lifetime in the troposphere than CH4 and CO2, and a lifetime of 116 years in the atmosphere. The global warming potential and uncertainty of N2O are 273 times and 128 times that of CO2. Industrial emissions of nitric acid, adipic acid and the like are the main sources of N2O, and how to efficiently convert or remove N2O has become an important issue in environmental governance.
[0003] As a core chemical for modern industry and agriculture, ammonia (NH3) is widely used in fertilizer production, energy carriers and chemical raw materials. However, the current synthesis of ammonia mainly relies on the Haber-Bosch process, which requires high temperature and high pressure conditions and consumes a large amount of fossil fuels, resulting in significant CO2 emissions. Therefore, it is urgent to develop efficient and sustainable ammonia synthesis technology under mild conditions.
[0004] As an emerging technology, electrochemical catalytic reduction can realize low-energy consumption and low-carbon emission chemical conversion at room temperature and pressure by driving the reaction with renewable energy. Through catalyst design, electrocatalysis can convert N2O and other nitrogen-containing gases into harmless products (such as nitrogen) and high-value-added products (such as ammonia). Li et al. designed a copper single-atom catalyst and converted N2O into N2 through electrocatalytic reduction under alkaline conditions, showing high conversion rate and selectivity (Li Z, Wu YS, Wang Het al. High-Efficiency Electrocatalytic Reduction of N2O with Single-Atom Cu Supported on Nitrogen-Doped Carbon [J]. Environmental Science & Technology, 2024, 58: 8976-8987). Wu et al. designed a double-atom Fe catalyst through theoretical calculation and applied it to the electrocatalytic reduction of N2O, showing high Faraday efficiency of N2O to NH3 (Wu D, Chen K, Lv P et al. Direct Eight-Electron N2O Electroreduction to NH3 Enabled by an Fe Double-Atom Catalyst [J]. Nano Letters, 2024, 24: 8502-8509). Cobalt-based catalysts have unique electronic structure and adjustable coordination environment, showing excellent activity and selectivity in CO2 reduction, N2 reduction and other electrocatalytic reactions. In addition, cobalt-based materials have low cost and high stability, and have the potential for large-scale application. However, there is no research on the application of cobalt-based catalysts in the electrocatalytic reduction of N2O to NH3, and there is no research on the co-conversion of N2O and CO2 to urea, and the reaction mechanism and performance optimization still need further research. SUMMARY
[0005] To overcome the problems of large amount of heat removal and possible secondary pollution of traditional N2O, NO x To overcome the problems of large amount of heat removal and possible secondary pollution of traditional N2O, NO
[0006] The present application first provides a preparation method of a cobalt-based catalyst, comprising the following steps:
[0007] (1) mixing a cobalt source, a carbon-nitrogen-containing compound, a precipitant and a solvent to react to obtain a precursor solution;
[0008] (2) placing the precursor solution in a high-pressure reaction kettle for hydrothermal reaction, and the obtained solid is the precursor;
[0009] (3) pyrolyzing the precursor in an inert atmosphere to obtain a cobalt-based catalyst.
[0010] In the preparation method, the cobalt source is at least one of dimethyl cobalt, cobalt acetylacetonate, cobalt chloride, cobalt acetate and cobalt oxalate;
[0011] The carbon-nitrogen-containing compound is at least one of dopamine hydrochloride, polyvinylpyrrolidone, urea, biochar and polypyrrole; preferably dopamine hydrochloride;
[0012] The precipitant is at least one of ammonia, sodium hydroxide, potassium hydroxide, ammonium carbonate and ammonium bicarbonate;
[0013] Specifically, the mass percentage concentration of the ammonia is 28%;
[0014] The molar ratio of the cobalt source, the carbon-nitrogen-containing compound and the precipitant is 1:(1-10):(10-20); specifically, 1:1:15;
[0015] In step (1), the reaction condition is stirring at room temperature for 0.5-2h, specifically 0.75h.
[0016] In the preparation method, step (1) specifically includes the following: dissolving the cobalt source in solvent 1 to obtain solution A; dissolving the carbon-nitrogen-containing compound in solvent 2 to obtain solution B; mixing the solution A and the solution B, then adding the precipitant, and stirring at room temperature for 0.5-2h to obtain the precursor solution.
[0017] Specifically, the solvent 1 can dissolve the cobalt source, and the solvent 2 can dissolve the carbon-nitrogen-containing compound;
[0018] In an embodiment of the present application, the cobalt source is cobalt acetate, the solvent 1 is anhydrous ethanol; the carbon-nitrogen-containing compound is dopamine hydrochloride, and the solvent 2 is water;
[0019] The mass ratio of the cobalt source and the solvent 1 is 1:(90-110); specifically, 1:103;
[0020] The mass ratio of the carbon-nitrogen-containing compound and the solvent 2 is 1:(10-20); specifically, 1:13;
[0021] In the preparation method, in step (2), the temperature of the hydrothermal reaction is 120-180℃, specifically 150℃;
[0022] The time of the hydrothermal reaction is 2-6h, specifically 4h.
[0023] In the preparation method, in step (3), the inert atmosphere is a nitrogen and / or argon atmosphere;
[0024] The temperature of the pyrolysis treatment is 600-1000℃; preferably 800℃;
[0025] The time of the pyrolysis treatment is 1-3h, specifically 2h;
[0026] The heating rate of the pyrolysis treatment is 4-6℃ / min.
[0027] In the above preparation method, the solid-liquid separation in step (2) is performed by filtration and / or centrifugation; specifically, filtration.
[0028] In step (2), the solid is washed with ethanol and water, and then dried.
[0029] Specifically, the drying temperature is 60℃, and the drying time is 10-30h; specifically, 24h.
[0030] Secondly, the present application provides a cobalt-based catalyst prepared by the above preparation method.
[0031] Thirdly, the present application further provides an application of the above cobalt-based catalyst in electrocatalytic ammonia production from nitrogen-containing compounds.
[0032] Specifically, the nitrogen-containing compound is at least one of N2O, NO and NO2.
[0033] Fourthly, the present application provides an application of the above cobalt-based catalyst in electrocatalytic ammonia production from N2O and / or NO x in the treatment of waste gas from nitric acid and / or adipic acid plants and / or purification of flue gas from solid waste combustion.
[0034] Specifically, x in NO x is 1 or 2.
[0035] Finally, the present application provides an application of the above cobalt-based catalyst in the synergistic electrocatalytic production of urea from N2O and CO2.
[0036] In the above application, the cobalt-based catalyst is coated on carbon paper as a cathode for electrocatalytic reaction. The carbon paper is hydrophilic carbon paper or hydrophobic carbon paper.
[0037] In the above application, the electrolyte for electrocatalysis is a mixed solution containing potassium hydroxide and potassium sulfate; the anode is a platinum sheet or a platinum mesh;
[0038] N2O, NO x is continuously introduced into the cathode chamber to provide a reaction environment.
[0039] In some embodiments of the present application, the pH of the electrolyte is 14; in the electrolyte, the concentration of potassium hydroxide is 1 mol / L, and the concentration of potassium sulfate is 0.1 mol / L.
[0040] The cobalt-based electrocatalyst of the present application is prepared by preparing a precursor solution containing a cobalt-containing material and a carbon-nitrogen compound, and then performing hydrothermal treatment and pyrolysis; the precursor solution contains a cobalt-containing material, a carbon-nitrogen compound and a precipitant. The cobalt-based catalyst prepared by the present application is first applied to the electrocatalytic conversion of nitrogen-containing compounds to NH3, and exhibits excellent catalytic activity. BRIEF DESCRIPTION OF DRAWINGS
[0041] Figure 1 XRD pattern of the NC-800 catalyst prepared for Comparative Example 1;
[0042] Figure 2 XRD pattern of the Co NPs in Comparative Example 2;
[0043] Figure 3 XRD pattern of the Co3O4 prepared for Comparative Example 3;
[0044] Figure 4 XRD pattern of the Co / NC-0 prepared for Comparative Example 4;
[0045] Figure 5 SEM pattern of the Co / NC-800 catalyst prepared for Example 1;
[0046] Figure 6 TEM pattern of the Co / NC-800 catalyst prepared for Example 1;
[0047] Figure 7 XRD pattern of the Co / NC-800 catalyst prepared for Example 1;
[0048] Figure 8 XRD pattern of the Co / NC-700 catalyst prepared for Example 2;
[0049] Figure 9 XRD pattern of the Co / NC-900 catalyst prepared for Example 3;
[0050] Figure 10 XRD pattern of the Co-PDA-900 catalyst prepared for Comparative Example 5;
[0051] Figure 11 N2O electrocatalytic reduction performance of the catalysts prepared for Examples 1-3;
[0052] Figure 12 N2O electrocatalytic reduction performance of the catalysts prepared for Comparative Examples 1-5;
[0053] Figure 13 N2O electrocatalytic ammonia production performance of the catalysts prepared for Examples 1-3 and Comparative Examples 1-5;
[0054] Figure 14 A plot of the electrocatalytic ammonia production performance of the catalyst prepared in Example 1 for different nitrogen oxides;
[0055] Figure 15 A plot of the reduction stability performance of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0056] The application will be further described in conjunction with the specific embodiments, and the examples given are only for the purpose of illustrating the application, but not for limiting the scope of the application.
[0057] In the following examples, the experimental methods are all conventional methods unless otherwise specified.
[0058] In the following examples, the quantitative tests are all set up in triplicate unless otherwise specified, and the results are averaged.
[0059] In the following examples, the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0060] Unless otherwise specified, the units used in the present specification are international standard units, and the numerical values and numerical value ranges appearing in the present application should be understood as including the systematic errors that are inevitable in industrial production.
[0061] In the present specification, the meaning of "may" includes both the meaning of performing a certain process and the meaning of not performing a certain process.
[0062] In the present specification, the "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", and the like refer to the specific elements (for example, features, structures, properties, and / or characteristics) described in relation to the embodiments, which are included in at least one embodiment described herein, and can be present in other embodiments or can not be present in other embodiments. In addition, it should be understood that the elements can be combined in various embodiments in any suitable manner.
[0063] In the present specification, the numerical value range represented by "numerical value A-numerical value B" refers to a range including the end point numerical values A, B.
[0064] In the present specification, when "room temperature" is used, the temperature is 25℃±5℃.
[0065] The present application is to overcome the problems of the conventional N2O, NO x To remove the problems of requiring a large amount of heat and possibly causing secondary pollution, a preparation method of a cobalt-based catalyst is first provided, comprising the following steps:
[0066] (1) mixing a cobalt source, a carbon-nitrogen-containing compound, a precipitant and a solvent to react, to obtain a precursor solution;
[0067] (2) placing the precursor solution in a high-pressure reactor to perform a hydrothermal reaction, and the obtained solid is a precursor;
[0068] (3) pyrolyzing the precursor in an inert atmosphere to obtain a cobalt-based catalyst.
[0069] The cobalt source is at least one of cobaltocene, cobalt acetylacetonate, cobalt chloride, cobalt acetate and cobalt oxalate;
[0070] The carbon-nitrogen-containing compound is at least one of dopamine hydrochloride, polyvinylpyrrolidone, urea, biochar and polypyrrole; preferably dopamine hydrochloride;
[0071] The precipitant is at least one of ammonia, sodium hydroxide, potassium hydroxide, ammonium carbonate and ammonium bicarbonate;
[0072] The molar ratio of the cobalt source, the carbon-nitrogen-containing compound and the precipitant is 1:(1-10):(10-20);
[0073] In step (1), the reaction conditions are stirring at room temperature for 0.5-2h.
[0074] In step (2), the temperature of the hydrothermal reaction is 120-180℃;
[0075] The time of the hydrothermal reaction is 2-6h.
[0076] In step (3), the inert atmosphere is a nitrogen and / or argon atmosphere;
[0077] The temperature of the pyrolysis is 600-1000℃; preferably 800℃;
[0078] The time of the pyrolysis is 1-3h;
[0079] The heating rate of the pyrolysis is 4-6℃ / min.
[0080] Secondly, the present application provides a cobalt-based catalyst prepared by the above preparation method.
[0081] Thirdly, the present application further provides an application of the above cobalt-based catalyst in electrocatalysis of nitrogen-containing compounds to produce ammonia.
[0082] Specifically, the nitrogen-containing compound is at least one of N2O, NO and NO2.
[0083] Fourthly, the present application provides an application of the above cobalt-based catalyst in N2O and / or NO xapplication in electrocatalytic ammonia production.
[0084] Finally, the application provides the application of the above-mentioned cobalt-based catalyst in the synergistic electrocatalytic production of urea from N2O and CO2.
[0085] The cobalt-based electrocatalyst of the application is applied for the first time in the electrocatalytic conversion of N2O to NH3, and exhibits excellent catalytic activity. Especially, the Co / NC-800 catalyst realizes NH3 production rate of 58.73 mgmg mental -1 h -1 and NH3 Faraday efficiency of 48.08% at-0.25 V (Vs. RHE).
[0086] From the results of the stability test, it can be seen that when the gas introduced is argon, the system current density of the Co / NC-800 catalyst is low, and after N2O is introduced, the system current density increases, indicating that N2O is electrocatalytically converted. After 5 times of gas switching, it still exhibits high Faraday efficiency and NH3 production rate, indicating that the Co / NC-800 catalyst has good stability.
[0087] Preparation of Comparative Example 1, NC-800 catalyst
[0088] 1 mL of 28wt% ammonia water, 40 mL of anhydrous ethanol and 90 mL of ultrapure water were mixed and stirred for 0.5 h to obtain solution A; 0.5 g of dopamine hydrochloride was dissolved in 10 mL of ultrapure water to obtain solution B. Solution B was added to solution A and stirred for 30 h to obtain a uniform mixture. The mixture was filtered and washed, and the black sample filtered was placed in a 60℃ vacuum drying oven and dried for 24 h to obtain a precursor. The precursor was placed in a nitrogen atmosphere, heated to 800℃ at a rate of 5℃ / min, and pyrolyzed at 800℃ for 2 h to obtain the NC-800 catalyst. The XRD pattern of the NC-800 catalyst is shown in Figure 1 From Figure 1 it can be seen that the NC-800 catalyst prepared in this comparative example exhibits a typical X-ray diffraction spectrum of C.
[0089] Comparative Example 2, cobalt nanoparticles Co NPs
[0090] The Co NPs in Comparative Example 2 were commercially purchased (particle size ≤ 500 nm, CAS: 7440-48-4 (powder), Aldrich), and the size was less than 500 nm. The XRD pattern of the Co NPs is shown in Figure 2 From Figure 2 it can be seen that the Co NPs at 41.6, 44.7, 47.5 and 75.9° respectively belong to the 100, 111, 101 and 220 crystal planes of cobalt.
[0091] Preparation of Comparative Example 3, Co304
[0092] Co304was prepared according to the following procedure. 2.9 g of cobalt nitrate hexahydrate was dissolved in 60 mL of ultrapure water to form solution A; 2 g of ammonium carbonate was dissolved in 20 mL of ultrapure water to form solution B; solution B was added dropwise to solution A at a rate of 3 mL / min, stirred for 2 h, and left to stand for 12 h; the precipitate was washed by suction filtration and the precipitate was dried at 60 °C for 24 h to obtain a precursor. The precursor was placed in an air atmosphere and heated to 500 °C at a rate of 5 °C / min and pyrolyzed at 500 °C for 4 h to obtain Co304. The XRD pattern of the Co304is shown in FIG. 2. From the XRD pattern, it can be seen that the Co304prepared in this comparative example exhibits typical Co304diffraction peaks, demonstrating the successful synthesis of Co304. Figure 3 Figure 3
[0093] Preparation of Comparative Example 4, Co / NC-0
[0094] Co / NC-0 was prepared according to the following procedure. 0.498 g of cobalt acetate tetrahydrate was dissolved in 65 mL of anhydrous ethanol to obtain solution A; 0.379 g of dopamine hydrochloride was dissolved in 5 mL of ultrapure water to obtain solution B; solution B was added to solution A, 2 mL of 28 wt% ammonia water was added, and the mixture was stirred at room temperature for 0.75 h to obtain a precursor solution. The precursor solution was placed in a high-pressure reaction kettle and heated in a 150 °C blast drying oven for 4 h; after natural cooling, the mixture was washed by suction filtration and washed three times with ethanol and water alternately; the black sample obtained by suction filtration was dried in a 60 °C vacuum drying oven for 24 h to obtain Co / NC-0. The XRD pattern of the Co / NC-0 is shown in FIG. 3. From the XRD pattern, it can be seen that the Co / NC-0 prepared in this comparative example contains cobalt elements, but no diffraction peaks related to Co appear. Figure 4 Figure 4
[0095] Preparation of Example 1, cobalt-based catalyst (Co / NC-800)
[0096] Co / NC-800 catalyst was prepared according to the following procedure. 0.498 g (2 mmol) of cobalt acetate tetrahydrate was dissolved in 65 mL of anhydrous ethanol to obtain solution A; 0.379 g (2 mmol) of dopamine hydrochloride was dissolved in 5 mL of ultrapure water to obtain solution B; solution B was added to solution A, 2 mL of 28 wt% ammonia water (30 mmol) was added, and the mixture was stirred at room temperature for 0.75 h to obtain a precursor solution. The precursor solution was placed in a high-pressure reaction kettle and heated in a 150 °C blast drying oven for 4 h; after natural cooling, the mixture was washed by suction filtration and washed three times with ethanol and water alternately; the black sample obtained by suction filtration was dried in a 60 °C vacuum drying oven for 24 h to obtain a precursor. The precursor was placed in a nitrogen atmosphere and heated to 800 °C at a rate of 5 °C / min and pyrolyzed at 800 °C for 2 h to obtain Co / NC-800 catalyst.
[0097] The SEM image of the Co / NC-800 catalyst is shown below. Figure 5 As shown. From Figure 5 It can be seen that the Co / NC-800 catalyst prepared in this embodiment is spherical, and there are circular spots of different sizes on the surface of the spheres, which may be caused to some extent by the formation of cobalt nanoparticles.
[0098] TEM image of the Co / NC-800 catalyst is shown below. Figure 6 As shown. From Figure 6 It can be seen that the prepared Co / NC-800 catalyst has a spherical structure, with the active component cobalt mainly located inside and encapsulated by a carbon layer on the outside. Cobalt, as the main active component, participates in the reaction of N2O and NO. x Electrocatalytic reactions, with carbon layers encapsulating and confining the active components to prevent loss, are the main reason for their good stability.
[0099] The XRD pattern of the Co / NC-800 catalyst is shown below. Figure 7 As shown. By Figure 7 It can be seen that the diffraction peaks at 44.2, 51.5 and 75.8° belong to the 111, 200 and 220 crystal planes of cobalt, respectively.
[0100] Example 2: Preparation of cobalt-based catalyst (Co / NC-700)
[0101] The preparation method of the Co / NC-700 catalyst in this embodiment is the same as that in Example 1, except that the pyrolysis temperature is 700℃.
[0102] The XRD pattern of the Co / NC-700 catalyst prepared in this example is shown below. Figure 8 As shown. By Figure 8 It can be seen that the diffraction peaks at 44.2, 51.5 and 75.8° belong to the 111, 200 and 220 crystal planes of cobalt, respectively. Their peak intensities are not as strong as those in Example 1, which may be the reason for the decrease in activity.
[0103] Example 3: Preparation of cobalt-based catalyst (Co / NC-900)
[0104] The preparation method of the Co / NC-900 catalyst in this embodiment is the same as that in Example 1, except that the pyrolysis temperature is 900℃.
[0105] The XRD pattern of the Co / NC-900 catalyst prepared in this example is shown below. Figure 9 As shown. By Figure 9 It can be seen that the diffraction peaks at 44.2, 51.5 and 75.8° belong to the 111, 200 and 220 crystal planes of cobalt, respectively.
[0106] Preparation of Comparative Example 5, cobalt-based catalyst (Co-PDA-900)
[0107] ZIF-67 preparation method: first, 1.745 g of cobalt nitrate hexahydrate was dissolved in 40 mL of methanol to obtain solution A; then 1.97 g of 2-methylimidazole was dissolved in 40 mL of methanol to obtain solution B; solution A was poured into solution B, stirred at room temperature for 20 h, and then filtered and washed (ethanol, water alternating washing 3 times); the obtained solid was placed in a vacuum drying oven and dried at 60 °C for 20 h to obtain a ZIF-67 sample. 1.21 g of tris(hydroxymethyl)aminomethane hydrochloride (tris (CAS: 1183-53-1, Aldrich)) was dissolved in 80 mL of ultrapure water, and the pH was adjusted to 8.5 by hydrochloric acid to prepare a tris-buffer solution; 2 g of ZIF-67 material was added to 80 mL of tris-buffer solution and stirred uniformly, then 4 g of dopamine hydrochloride was added, and stirred for 24 h; the obtained solid was washed by centrifugation with water and ethanol alternately three times, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain a precursor. The precursor was placed in a nitrogen atmosphere, heated to 900 °C at a rate of 5 °C / min, and kept at 900 °C for 2 h for pyrolysis treatment to obtain a Co-PDA-900 catalyst.
[0108] The XRD pattern of the Co-PDA-900 catalyst is shown in FIG. 1. Figure 10 As can be seen, the diffraction peaks of the Co-PDA-900 catalyst prepared in this comparative example at 41.6, 44.7, 47.5 and 75.9° are respectively attributed to the 100, 002, 101 and 110 crystal planes of cobalt. Figure 10
[0109] Example 5, N2O, NO x Electrocatalytic reduction performance test
[0110] Take 0.25 mg of each catalyst of Examples 1-3 and Comparative Examples 1-5, respectively, in a sample bottle containing 950 uL of anhydrous ethanol, then add 50 uL of Nafion 117 perfluorinated resin solution (CAS: 31175-20-9, Maclin), ultrasonic for 30 min to obtain an ink solution, take 25 uL of the ink solution and uniformly coat on 1 cm x 1 cm hydrophobic carbon paper (H-type electrolytic cell) / 1 cm x 1 cm conductive carbon paper treated with PTFE (39BB, Sigracet) (flow cell), and after natural drying, use it as a cathode, and use Pt as an anode, respectively, in an H-type double-chamber electrolytic cell or a flow cell, and use a saturated mercury potassium sulfate electrode as a reference electrode. The reaction solution has a pH of 14, contains 1 mol / L potassium hydroxide and 0.1 mol / L potassium sulfate, and the solvent is water. For the H-type electrolytic cell, first pass Ar gas into the cathode chamber at a flow rate of 30 mL / min for 30 min, test the LSV curve, then switch the gas to N2O or NO x , keep the flow rate unchanged, and keep it for 1 h, and test the LSV curve. For the flow cell, the cathode chamber is aerated with Ar or N2O or NO x at a flow rate of 30 mL / min. For the flow cell, the electrolyte flow rate is controlled at 5 mL / min, first pass Ar gas into the cathode chamber at a flow rate of 10 mL / min for 5 min, then apply a constant voltage, after 30 min, take 10 mL of cathode liquid for product testing; then, switch the gas to N2O or NO x , and keep the rest of the operation steps unchanged. The voltage range is 0 to -0.6 V (vs. RHE) under the condition of starting N2O or NO x electrocatalytic conversion reaction, and the product NH3 is analyzed by ultraviolet spectrophotometry, and the results are shown in Figures 11-14 , wherein Figure 11 and Figure 12 are tested by using an H-type electrolytic cell, Figure 13 and 14 are tested by using a flow cell.
[0111] It can be seen from Figure 11 and 12 that compared with other catalysts, the Co / NC-800 catalyst shows the largest current difference under Ar and N2O atmosphere. This result shows that the cobalt-based catalyst prepared by the present application can be effectively applied to the electrocatalytic conversion of N2O, Figure 13 which further proves this point. It can be seen from Figure 13 that compared with other catalysts, the Co / NC-800 catalyst shows the largest ammonia yield and Faraday efficiency. Figure 14 shows that the Co / NC-800 catalyst shows excellent electrocatalytic ammonia yield and Faraday efficiency for N2O and NO x .
[0112] Example 6, Catalyst stability test
[0113] Co / NC-800 catalyst prepared in Example 1 was coated on 1 cm x 1 cm PTFE treated conductive carbon paper (39BB, Sigracet) as cathode, Pt as anode, and saturated calomel electrode as reference electrode. They were placed in the flow cell electrolysis cell respectively. The reaction solution was pH 14, containing 1 mol / L potassium hydroxide and 0.1 mol / L potassium sulfate, and water as solvent; Ar, N2O gas flow was maintained at 10 mL / min, and electrolyte flow was controlled at 5 mL / min. N2O electrocatalytic conversion reaction was started at a voltage of -0.25 V (Vs. RHE). The stability was tested by switching the gas (Ar, N2O), and the results are shown in Figure 15 . From Figure 15 It can be seen that when the gas is argon, the system current density is low, and after N2O is introduced, the system current density increases, indicating that N2O is electrocatalytically converted. After 5 times of gas switching, it still shows high Faraday efficiency and NH3 yield, indicating that the Co / NC-800 catalyst has good stability.
[0114] The above description of the examples is only to help understand the method of the present application and its core idea. Various modifications to these examples will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other examples without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these examples shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a cobalt-based catalyst, characterized in that: The preparation method includes the following steps: (1) A cobalt source, a carbon-nitrogen compound, a precipitant and a solvent are mixed and reacted to obtain a precursor solution; (2) The precursor liquid is placed in a high-pressure reactor for hydrothermal reaction, and the resulting solid is the precursor. (3) The precursor is pyrolyzed in an inert atmosphere to obtain a cobalt-based catalyst.
2. The preparation method according to claim 1, characterized in that: The cobalt source is at least one of cobalt decene, cobalt acetylacetonate, cobalt chloride, cobalt acetate, and cobalt oxalate. The carbon-nitrogen compound is at least one of dopamine hydrochloride, polyvinylpyrrolidone, urea, biochar, and polypyrrole; The precipitant is at least one of ammonia, sodium hydroxide, potassium hydroxide, ammonium carbonate, and ammonium bicarbonate. The molar ratio of the cobalt source, carbon-nitrogen compound, and precipitant is 1:(1-10):(10-20); In step (1), the reaction is carried out under the condition of stirring at room temperature for 0.5-2 hours.
3. The preparation method according to claim 1, characterized in that: Step (1) specifically includes the following: dissolving the cobalt source in solvent 1 to obtain solution A; dissolving the carbon-nitrogen compound in solvent 2 to obtain solution B; mixing solution A and solution B, then adding the precipitant, and stirring at room temperature for 0.5-2 hours to obtain the precursor solution.
4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 120-180℃; The hydrothermal reaction takes 2-6 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the inert atmosphere is a nitrogen and / or argon atmosphere; The temperature of the pyrolysis treatment is 600-1000℃; The pyrolysis treatment time is 1-3 hours; The heating rate of the pyrolysis treatment is 4-6℃ / min.
6. The preparation method according to claim 6, characterized in that: In step (3), the temperature of the pyrolysis treatment is 800℃.
7. The cobalt-based catalyst prepared by the preparation method according to any one of claims 1-6.
8. The application of the cobalt-based catalyst according to claim 7 in the electrocatalytic production of ammonia from nitrogen-containing compounds.
9. The cobalt-based catalyst of claim 7 in the treatment of waste gas from nitric acid and / or adipic acid plants and / or the purification of exhaust gas from solid waste combustion, for the removal of N2O and / or NO. x Its application in electrocatalytic ammonia production.
10. The application of the cobalt-based catalyst according to claim 7 in the synergistic electrocatalytic production of urea from N2O and CO2.
